Bio-based materials for repairing cracks in concrete : an experimental study - Prima Yane Putri (UNP PRESS, 2020)
ISBN : 978-602-1178-69-0 Bio-based materials for repairing cracks in concrete : an experimental study Recently, liquid-based repair techniques in the field of self-healingthrough the use of microbial inducedcalcium carbonateprecipitation(MICP) havebeen intensively investigated. The mixturesaretypicallycomprisedof a microorganism, an organic carbonsource and a calciumsource which is readily available in concrete. When dry yeastis selectedas the microorganism, carbon dioxide produced through the microbialmetabolic processes consuming an organic carbon source such asglucose provides carbonate ions. The carbonate ions lead to react withcalcium ions present in the mixture, leading to the precipitation ofcalcium carbonatedependson the pH levels in the alkalineenvironment.It shouldbe notedthat the material produced through the reactions is notharmful to concrete materials because the precipitatesare mainlycomprisedof calcium carbonate which is one of the reaction productsformed by carbonation of hydration products. Besides the materialproperties, the mixture is a less viscous material compared toconventional materialssuch as epoxy resin.Thismay overcomeshortcomings associated with theconventionalrepair materials asmentioned previously. Thus, it would be beneficial if the mixturespenetrate into deeper zones of gaps formed between concrete membersand couldeffectivelyimprove the water tightness of concrete withdefects.In this research, the applicability ofyeast-based mixturesfor concreterepair hasbeen studied. This technique employs yeast, glucose andcalcium acetate mixed inTrisbuffer solution.The microbialmetabolicprocessleads to precipitation of calcium carbonate.Influencing factorson the precipitation rate depending on the constituents ofyeast-basedmixturesinvolving types of dry yeast andtheconcentration ofyeast-based mixtureswere studied.The influence of temperature on theprecipitation rate was also examined for practical application.Initially,tubeprecipitation testmethodwas conductedfor investigatingthe pH andtheprecipitation rate of calcium carbonate by measuringfiltered paper. Then, calcium ions producedin the mixtureweremeasuredby commercially available meter (calcium ion electrode model viCA-2031)tocalculatethe decreasing rate of calcium ions in test tubes.Theresult showed that thedecreasing rate of calcium ionshas a goodcorrelation with the precipitation rate of calcium carbonate measuredusing thefiltered paper. The decreasing rate of calcium ions wasalmostequal tothe amount ofprecipitation of calcium carbonate. Therefore,largerdecreasing rate of calcium ionsat early stages of the testsmeansthat the precipitation rate of calcium carbonate is higher. In thisthesis,thedecreasing rate of calcium ionsis usedas an index oftheprecipitationrate of calcium carbonateunder the test tube conditions.Wholeseries of the experiment in this studywere studied based onspecific objectivesofeach experiment.The several factors affecting theprecipitation rate of calcium carbonatewere examined in each chapter.First, this studyinvestigated the effects ofchangesoftemperature toincreasethe precipitation rate of calcium carbonate inmixturestested.The second series of experimentswas performed to examine the effectsof dry yeastâ€™s type to enhance the precipitation rate of the calciumcarbonate.In order toassess the influence oftypesof dry yeast, Fourier-Transformed Infra-Red spectroscopy (FT-IR) analysiswas used.Thethird series of experiment was conducted to evaluate the influence ofdifferentconcentration ofyeast-based mixtureson calcium carbonateprecipitation.Finally, this study observed the applicability oftheyeast-based mixturesfor repairing water leakage in concrete specimens.Basedon the result ofseriesexperiments carried out, thebest composition ofyeast-based mixtureswith the highest precipitation rate of calciumcarbonate was selected. Furthermore, water permeability test wasconducted on theconcreteleakage to determine the flow rate andeffectiveness of theyeast-based mixturesapplication.This research was supported by Grant-in-Aid for Scientific Research(B):15H04025 and Grant for Penelitian Dasar Universitas Negeri Padangin2019and2020. Authors greatly appreciate for the financial supports. Â© 2020 UNP Press